The Influence of Social Media on Mathematics Learning Achievement in Mathematics Education Students - Wulan Lailatul Mufidah; Raifatul Maghfiroh; Moh. Syadidul Itqan; Rebecca L. Morrison (CV Edujavare Publishing, 2025)
This study aims to examine the influence of social media usage on mathematics learning achievement among students of the Mathematics Education Study Program at Nurul Jadid University. In the digital era, social media has become an integral part of students' academic lives. The research employed a quantitative approach using a correlational method. Data were obtained through a Likert-scale questionnaire distributed to 28 sixth-semester students and analyzed using simple linear regression. The results of the normality test indicated that the data were normally distributed and suitable for further analysis. The regression analysis revealed that social media usage had a positive and significant effect on mathematics learning achievement, with a correlation coefficient of 0.747 and a determination coefficient of 55.8%. This means that more than half of the variance in learning achievement can be explained by the intensity of social media usage. These findings suggest that productive and focused use of social media can enhance conceptual understanding, active engagement in discussions, and overall learning effectiveness in mathematics. Therefore, the integration of social media into the learning process must be supported by digital literacy and guided by lecturers to prevent it from becoming a distraction.